2018
DOI: 10.1080/15287394.2017.1415579
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to firework chemicals from production factories in pregnant women and risk of preterm birth occurrence in Liuyang, China

Abstract: In the production of fireworks, various pollutants including particles of metals and organic compounds are released into the environment. Although the adverse effects of these air pollutants are known, the impact on pregnant women residing in this area remains to be determined. The aim of this study was to examine the association between maternal exposure to fireworks production chemicals and frequency of preterm birth in Liuyang, China. Maternal exposure to fireworks production was estimated at the residentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A cohort study performed by Cakmak et al in Canada found that exposure to higher road density and proximity to major traffic roads were related to increased COPD mortality (28). However, they selected the length of local roads within a 200 m radius of postal code centroid rather than residential distance to the closest road as indicator, which might explain part of the geographical heterogeneity observed since different traffic parameters led to various sensitivity in estimates of exposure (11). The discrepancy between the results of residential proximity to highway and road might be due to a wide emission range of pollutants on expressways and a declined concentration with increasing distance (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort study performed by Cakmak et al in Canada found that exposure to higher road density and proximity to major traffic roads were related to increased COPD mortality (28). However, they selected the length of local roads within a 200 m radius of postal code centroid rather than residential distance to the closest road as indicator, which might explain part of the geographical heterogeneity observed since different traffic parameters led to various sensitivity in estimates of exposure (11). The discrepancy between the results of residential proximity to highway and road might be due to a wide emission range of pollutants on expressways and a declined concentration with increasing distance (29).…”
Section: Discussionmentioning
confidence: 99%
“…When the exposure concentration was highly spatially and geographically heterogeneous, mis-estimation of exposures would be introduced into analysis (9). In recent years, multi-pollutant indicators have been adopted to investigate the association with health outcomes to better evaluate realworld exposure to pollutants such as residential distance to the closest roads (10), factory density (11), and traffic density (12). Residential proximity to road has been found to be a good proxy for traffic-related air pollutant concentrations (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, another study found an association between PM 10 and PTB only for primiparous mothers when exposed to emissions from a waste incinerator [ 34 ]. Some other studies have also examined the associations of fireworks factories [ 63 ] and coke works [ 64 ] with PTB and LBW, respectively, but no associations appeared.…”
Section: Resultsmentioning
confidence: 99%
“…In the United States and Canada pregnant women were found to contain detectable levels of EC including polychlorinated biphenyls (PCB), organochlorine pesticides (OCP), perfluorinated compounds, phenols, polybrominated diphenylethers (PBDE), phthalates, polycyclic aromatic hydrocarbons (PAH), and perchlorate (Canadian environmental contaminants biomonitoring programs 2018; Woodruff, Zota, and Schwartz 2011). Several epidemiological and clinical studies demonstrated a link between EC exposure and increased risks of health impairments and diseases including neurological [Parkinson's (Chhillar et al 2013;Ismail et al 2017;Weisskopf et al 2010) and Alzheimer's (Richardson et al 2014)], reproductive (Han et al 2016;Karwacka et al 2017;Lenters et al 2015;Veras et al 2010), developmental (Li et al 2018;Torres-Sánchez et al 2013;Williams, Watson, and Desesso 2012), respiratory (0Gascon et al 2014), metabolic diseases (Vafeiadi et al 2016), as well as cancer (Bencko et al 2008;VoPham et al 2015). Recent epidemiological investigations reported positive correlations between exposure to persistent organic pollutants (PCB, OCP), metabolic diseases, and dyslipidemia in populations of Northern Canada (Inuits, First Nations from Northern Manitoba and Ontario) (Marushka et al 2018;Chan 2017, 2018).…”
Section: Introductionmentioning
confidence: 99%